Effect of timing of surgery on postoperative complications and prognosis in elderly patients with hip fractures - Zhuo, Zuobin; Hong, Weijun; Ma, Guangxi (Frontiers in Medicine, 2025)
BackgroundIn clinical practice, there is no standardized criteria for the optimal timing of hip fracture surgery in the elderly, and there is much controversy.ObjectivesTo investigate the effect of timing of surgery on postoperative complications and prognosis in elderly patients with hip fractures.MethodsRetrospectively analyzed 636 elderly hip fracture patients over 65 years old. The patients were divided into early group (< 3 days), intermediate group (3–7 days) and late group (> 7 days) according to the time from fracture to surgery, and the three groups were compared with the postoperative in-hospital general conditions, the occurrence of complications, the efficacy and the prognosis. p < 0.05 indicates that the difference is statistically significant.ResultsPostoperative hospitalization was significantly shorter in the early group than in the intermediate and late groups (9.5 ± 4.2 d vs. 11.9 ± 3.7 d vs. 13.3 ± 4.5 d, p < 0.05). The incidence of postoperative lung infection (2.7% vs. 6.3% vs. 8.4%), deep vein thrombosis (3.9% vs. 6.7% vs. 11.6%), stress ulcers (1.9% vs. 3.6% vs. 7.1%), and pressure ulcers (2.3% vs. 6.7% vs. 7.7%) was the lowest in the early group, followed by the intermediate group, and the highest in the late group (p < 0.05). In-hospital mortality was lower in the early group than in the intermediate and late groups (3.5% vs. 8.0% vs. 10.3%). In addition, at 1 month postoperatively, Harris scores were significantly higher in the early group than in the intermediate group (87.1 ± 5.3 vs. 82.2 ± 5.6, p < 0.001) and in the intermediate group than in the late group (82.2 ± 5.6 vs. 78.4 ± 5.0, p = 0.008). At 1 year postoperatively, the mortality rate was lower in the early group than in the intermediate and late groups (2.4% vs. 6.8% vs. 7.2%).ConclusionEarly surgery reduces the incidence of postoperative complications in elderly hip fracture patients, shortens hospitalization time, facilitates early recovery of hip function, and reduces mortality within 1 year after surgery.